If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -3(4x + 2) = 6(2x + 3) * 17 Reorder the terms: 7 + -3(2 + 4x) = 6(2x + 3) * 17 7 + (2 * -3 + 4x * -3) = 6(2x + 3) * 17 7 + (-6 + -12x) = 6(2x + 3) * 17 Combine like terms: 7 + -6 = 1 1 + -12x = 6(2x + 3) * 17 Reorder the terms: 1 + -12x = 6(3 + 2x) * 17 Reorder the terms for easier multiplication: 1 + -12x = 6 * 17(3 + 2x) Multiply 6 * 17 1 + -12x = 102(3 + 2x) 1 + -12x = (3 * 102 + 2x * 102) 1 + -12x = (306 + 204x) Solving 1 + -12x = 306 + 204x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-204x' to each side of the equation. 1 + -12x + -204x = 306 + 204x + -204x Combine like terms: -12x + -204x = -216x 1 + -216x = 306 + 204x + -204x Combine like terms: 204x + -204x = 0 1 + -216x = 306 + 0 1 + -216x = 306 Add '-1' to each side of the equation. 1 + -1 + -216x = 306 + -1 Combine like terms: 1 + -1 = 0 0 + -216x = 306 + -1 -216x = 306 + -1 Combine like terms: 306 + -1 = 305 -216x = 305 Divide each side by '-216'. x = -1.412037037 Simplifying x = -1.412037037
| X+2=2(3x-8) | | 14+19+x*3=17 | | 4a^3+6a^2+5a=0 | | 1+x=10-2x | | -6x-15=58 | | ax+b+cx=d | | 2x^2-4=60 | | x^2+2x(0.4)=0.84 | | -x+2y+4z=-11 | | f(x)=x^2+13x+37 | | B=pn+pforn | | 12x+2=(7)2x-3 | | 6p^2+25x+4=0 | | y=.33(x-27) | | 2.75f=24.5 | | 5-6lnx=20 | | (3x-c)(x-3)=12 | | 5n^2=-5n+160 | | 7s+8l=180 | | 4x-2=3(2x+5)-31 | | 5x-20=2x | | x+8y=29 | | 2t^3+13t+15t=0 | | y=9x^2+x+7 | | 4(8x+10)=32x-8 | | 9k+27=0 | | 2+3(-1)/6+(-7)+1= | | 9x+15=9x-15 | | 7+2s-5=8s+20-4s | | 4600=k(30) | | 4v+23v+28=0 | | 2s+8l=120 |